Immunization With Skp Delivered on Outer Membrane Vesicles Protects Mice Against Enterotoxigenic Escherichia coli Challenge - Hays, Michael P.; Houben, Diane; Yang, Yang; Luirink, Joen; Hardwidge, Philip R. (Frontiers in Cellular and Infection Microbiology, 2018)
Outer membrane vesicles (OMVs) are promising vaccine components because they combine antigen and adjuvant in a single formulation. Detoxified Salmonella enterica strains that express penta-acylated lipid A retain OMV immunogenicity but with reduced reactogenicity. We have previously shown that a recombinant form of the enterotoxigenic Escherichia coli (ETEC) seventeen kilodalton protein (Skp) protects mice in a pulmonary challenge model, when fused to the glutathione-S-transferase (GST) epitope and combined with cholera toxin. Here we compared directly the efficacy of expressing Skp in detoxified Salmonella OMVs to GST-Skp for their ability to protect mice against ETEC challenge. We observed that the display of Skp on OMVs, in the absence of exogenous adjuvant, protects the mice as well as the recombinant GST-Skp with adjuvant, showing that we can achieve protection when antigen and adjuvant are administered as a single formulation. Collectively, these data demonstrate the utility of using OMVs for the expression and display of antigens for use in vaccine development and validate previously published work demonstrating that immunization with Skp is efficacious in protecting mice against ETEC challenge.